2015
DOI: 10.1097/yic.0000000000000070
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in verbal memory following SSRI augmentation of antipsychotic treatment is associated with changes in the expression of mRNA encoding for the GABA-A receptor and BDNF in PMC of schizophrenic patients

Abstract: Verbal memory impairment in schizophrenia is associated with abnormalities in gamma-aminobutyric acid (GABA)-ergic and brain-derived neurotrophic factor (BDNF) systems. Recent evidence from animal and clinical studies that adding fluvoxamine to antipsychotics alters the expression of transcripts encoding for the GABA-A receptor and BDNF led us to postulate that fluvoxamine augmentation may improve memory in schizophrenia. To test this, we examined the effect of add-on fluvoxamine on verbal memory and other cog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…Our results are consistent with recent reports demonstrating that serum BDNF levels are lower in schizophrenia patients with deficit syndrome [8] and that BDNF mRNA expression is downregulated in various cortical areas in schizophrenia [18][19][20]. Some clinical studies recently reported a significant increase in BDNF transcript levels in peripheral mononuclear cells of schizophrenia patients following fluvoxamine augmentation of antipsychotics [21,22]. Here we found a significant negative correlation between serum BDNF level and PANSS score after ECT and medication.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are consistent with recent reports demonstrating that serum BDNF levels are lower in schizophrenia patients with deficit syndrome [8] and that BDNF mRNA expression is downregulated in various cortical areas in schizophrenia [18][19][20]. Some clinical studies recently reported a significant increase in BDNF transcript levels in peripheral mononuclear cells of schizophrenia patients following fluvoxamine augmentation of antipsychotics [21,22]. Here we found a significant negative correlation between serum BDNF level and PANSS score after ECT and medication.…”
Section: Discussionsupporting
confidence: 93%
“…Although (small) positive effects of APs on cognition have consistently been reported (Baldez et al, 2021; Keefe et al, 2007), our findings suggest that pharmacological interventions specifically aimed at noradrenergic and/or serotonergic systems might proof beneficial in terms of improving specific aspects of cognition in PSD and related disorders. While some evidence exists in that regard (Mancini et al, 2021; Silver et al, 2015), no clinical relevance of antidepressants in general was reported in a recent metanalysis of chronic SCZ patients (Vernon et al, 2014). However, the included studies were small, and cognitive outcomes were grouped within a-priori cognitive domains (EF, language, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Caution therefore needs to be taken when assessing serum BDNF as a reflection of brain BDNF in patients and ideally should be corroborated with other measures such as correlation with symptomology and changes in level in response to medication. However, despite some studies failing to find differences in serum BDNF levels between schizophrenia patients and controls (T. L. Huang and Lee, 2006;Shimizu et al, 2003), the majority consensus suggests palpable dysfunction in BDNF-TrkB signalling as being a fundamental aspect of pathophysiology in schizophrenia (Green et al, 2011). The common BDNF Val66Met polymorphism has also been found to be linked with aspects of schizophrenia symptomology e for example, the detrimental Met allele is associated with earlier disease onset (Chao et al, 2008).…”
Section: Schizophreniamentioning
confidence: 94%
“…G. Lee et al, 2010). The antidepressant fluvoxamine, when added as an adjunct treatment to antipsychotics in a recent study, improved associative and logical verbal memory and this improvement was correlated with increases in BDNF mRNA (Silver et al, 2015). Exercise has been shown to have beneficial effects on both positive and negative symptoms (Behere et al, 2011;Scheewe et al, 2013;Vancampfort et al, 2011) and memory performance in schizophrenia (Kimhy et al, 2015;Pajonk et al, 2010) as well as increasing BDNF (Kimhy et al, 2015;Kuo et al, 2013).…”
Section: Schizophreniamentioning
confidence: 96%